PARENTING: PENDAMPINGAN ORANGTUA TERHADAP SISWA KELAS VI DALAM MENGHADAPI UJIAN NASIONAL DI SD NEGERI OE’UE KECAMATAN KUATNANA TTS - yulsy marselina Nitte; Yanuaria Moru Kali; Yorika Nabut Nabut (FKIP Universitas Citra Bangsa, 2022)
Parenting is an activity of providing food (nourishing), providing guidance (guiding), in the form of protecting (protecting) children when they grow and develop. And one of the educational efforts can be in the form of mentoring (guiding) the readiness of children in facing the national exam. The activity is to provide assistance to the parents of grade VI students in facing the national exam. The method used is lecture and discussion. Itt is hoped that teachers, schools and especially parents can carry out their parenting activities to the fullest in assisting children in facing the national exam